(untitled) (Research, Society and Development, 2021)
This article will analyzed the issues arising from medical error in the modalities of criminal and civil liability as a result of aesthetic damage. Medical error comes from inappropriate professional behavior, which is therefore characterized by recklessness, malpractice or negligence, considering that technical non-compliance can damage the life or health of others. The doctor’s legal responsibility is divided into administrative, civil and criminal areas. In view of this issue, the article will discuss the responsibility for medical error in cosmetic plastic surgery in Brazil, seeking to understand how the punishment of this professional is adopted in view of this type of event. Thus, this work aims to carry out a brief analysis of medical civil and criminal liability arising from the error of the aesthetic procedure. For a better development of the work the method of deductive approach was used, while the technique was used the bibliographical research and the documental analysis. Through the research, it was found that the legal system regulates the issue of sanctions committed for medical errors since the damage caused by the physician’s activity configures, like any other, civil, criminal and disciplinary liability arising from an unlawful act or poor performance of service. Thus, it is up to the plastic surgeon to provide the patient with clear, complete, precise and intelligible information, so that he, knowing the risks arising from his decisions and the treatment pursued, assumes the responsibilities of his informed consent, and commits to follow the instructions for the postoperative period.